Effects of Visual Image Strategy on Students Speaking Skills : an Experimental Study at Secondary Level - Alifiah, Vina; Ghozali, Imam; Sabartono, Ribut (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2023)
This research aimed to show the impact of the Visual Image strategy on the students’ speaking skills at 10th grade at one of the private schools in Jember. The design of research used was quasi-experimental by forming 2 groups, Its Control, and Experimental group. To investigate the effectiveness of the visual image strategy, the researcher conducted an oral test with the first step is giving 2-3 treatments to the experimental group, then the researcher conducted a post-test to the control and experimental group which finally the scores of the two groups were compared through three steps (T-Table, T-test, and DRE). The results of this study can be input and motivation for teachers to determine students' speaking skills and can apply this strategy to learning English in the classroom.